Study of The Needs of The World of Work Industry For Graduates of Health Vocational High Schools - Nisa, Arofatin; Riyanto, Yatim; Soedjarwo, Soedjarwo (International Journal of Current Educational Research, 2025)
Objective: This study aims to describe the needs of the industry workforce for graduates of Health Vocational Schools. Method: This study employs a qualitative approach. Data collection is done through interviews, observations, and documentation studies. The object of this study is four industrial health facilities in the Surabaya area. The subjects of the study are health service business owners or personnel departments. Data analysis in qualitative research is carried out through four stages. Results: The challenging skill aspects required are the ability to operate a computer and good skills in each field of competence. Additional skills required are vital signs checks, monitoring child development, and basic childcare skills. The soft skills abilities required are teamwork, communication skills, leadership, networking, adaptability, friendliness, good work ethic, discipline, and empathy. Novelty: This study will examine the specific industrial needs of the workforce for graduates of Health Vocational High Schools, with a focus on the competency gap that still exists between the education curriculum and the demands of the healthcare industry. This study identifies the technical and non-technical skills most needed by companies in the health sector, thus providing new insights into improving the curriculum of Health Vocational High Schools.